Ghrelin and the Control of Energy Balance in Females - Smith, Andrea; Woodside, Barbara; Abizaid, Alfonso (Frontiers in Endocrinology, 2022)
Ghrelin is considered one of the most potent orexigenic peptide hormones and one that promotes homeostatic and hedonic food intake. Research on ghrelin, however, has been conducted predominantly in males and particularly in male rodents. In female mammals the control of energy metabolism is complex and it involves the interaction between ovarian hormones like estrogen, and metabolic hormones. In females, the role that ghrelin plays in promoting feeding and how this is impacted by ovarian hormones is not well understood. Basal ghrelin levels are higher in females than in males, and ghrelin sensitivity changes across the estrus cycle. Yet, responses to ghrelin are lower in female and seem dependent on circulating levels of ovarian hormones. In this review we discuss the role that ghrelin plays in regulating homeostatic and hedonic food intake in females, and how the effects of ghrelin interact with those of ovarian hormones to regulate feeding and energy balance.